Efficacy of using a complex of minerals and vitamins for prevention of complications in bone tissue and the digestive tract in rats with hypothyroidism - Makarenko, O. A.; Zaderei, O. V.; Maikova, H. V. (Regulatory Mechanisms in Biosystems, 2021)
Significant consequences of hypothyroidism are impairments in all types of metabolism, including bone metabolism, pathological changes in the digestive tract and the development of deficiency of vitamins, macro-and micronutrients.The relevance of the study is due to the widespread occurrence of hypothyroidism and the feasibility of developing effective methods for the prevention of the pathology and its complications. The study was aimed at the condition of bone tissue and digestive tract in rats with hypothyroidism, as well as the effectiveness of preventive addition of a complex of vitamins and minerals. The studies were performed on rats with hypothyroidism that was caused using thyrostatic mercazolyl for 50 days, administered orally. Prophylaxis was performed by adding a prophylactic complex of vitamins P, C, D and minerals Ca, Mg, Cu, Se, Mn to the daily diet. In the bone tissue of rats, the indicators of destruction (elastase and acid phosphatase activity) and mineralization (alkaline phosphatase activity, calcium content) as well as the antioxidant state (activities of catalase, glutathione reductase, malonic dialdehyde content) were studied. In the gums and mucous membranes of the digestive tract of rats, we determined indicators of antioxidant status (catalase activity, malonic dialdehydecontent), inflammation (activities of elastase, acid phosphatase) and dysbiosis (activities of urease activity, lysozyme). In the bone tissue of rats with hypothyroidism, activation of destruction processes, reduction of calcium levels, activation of lipid peroxidation and antioxidant enzymes were found. Hypothyroidism also led to pathological disorders in the gums of rats and gastric mucosa, small and large intestine, namely – the development of inflammation, increased membrane permeability, activation of lipid peroxidation, increased contamination with opportunistic bacteria against the background of reduced antioxidant protection. In general, preventive use of the complex contributed to the normalization of the studied parameters in the gums, mucous membranes of the stomach, intestines, as well as remodeling processes and antioxidant-prooxidative state in the bone tissue of animals with hypothyroidism. In the conditions of hypothyroidism, the proposed complex of vitamins and minerals provided notable antioxidant, anti-inflammatory and antidysbiotic effects in the tissues of the gastrointestinal tract, thus overcoming the calcium deficiency in the blood and stopping the destructive and oxidative processes in the bone tissue of animals with hypothyroidism.